Plan de negocio para la creación de una empresa de repostería saludable en el Municipio de Palmira Valle del Cauca (2022)
Through this project, a business plan is designed to create a healthy confectionery company in the city of Palmira, for which a market study was carried out in order to identify consumption trends in the sector.